STUDI MAQĀSHID AL-QUR’ĀN SIKLUS PERJALANAN HIDUP MANUSIA DALAM AL-QUR’AN - Ikmal; Khairul Muttaqin (REVELATIA: Jurnal Ilmu Al-Qur'`an dan Tafsir, 2021)
Maqāshid al-Qur’ān is an approach of interpretation study. This approach was developed to give a new viewpoint for mufassir to have more comprehensive understanding of the Qur'an contextually, as of it contributes much to life. Based on this, the aims of this article is to apply the concept of Maqāshid al-Qur'ān which was initiated by Imam Muammad al-Thāhir ibn 'Āsyūr in the verses of the human life cycle. The application of Maqāshid al-Qur’ān will reveal the meaning and moral message behind the verse with covering two issues, first is the cycle and phase of human life in the Qur'an, and second is the interpretation and moral message of the verse about the cycle of human life. This research was a library research with descriptive analysis method using the Maqāshid al-Qur'ān approach by Muhammad al-Thāhir ibn 'Āsyūr version. The results of the study showed that: first, the cycle and phase of the human life take place in five phases of life, there are the realm of the spirit, the realm of the womb, nature, the world, the grave, and the afterlife. Second, the result of the interpretation and moral message of the verse of the human life cycle is about the miracle of humans to have the right belief, akhlaq, ethics and good morals, and explaining the miracles of the Qur'an. The lessons for muslim is also discussed.